2016
DOI: 10.1093/jac/dkv444
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of an IncR plasmid carryingarmA,blaDHA-1andqnrB4fromKlebsiella pneumoniaeST37 isolates

Abstract: K. pneumoniae ST37 strains with an MDR IncR plasmid carrying armA, blaDHA-1 and qnrB4 were identified in a hospital in the USA, where these resistance genes remain rare. The IncR backbone may play a role in the global dissemination of these resistance genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 32 publications
2
18
0
Order By: Relevance
“…And our data indicated that ST37 were the main epidemic clones in the Neonate Ward, which showed consistency with what found in other studies [19,38]. It was discovered that ST37 are presumably to be a potential high-risk MDR K.pneumoniae clonal lineage [39].Furthermore, it is reported that carriage of carbapenem-resistant K. pneumoniae (CRKP) in the GI tract may precede and possibly serve as a source for subsequent clinical infections in approximately 9% of carriers [40,41]. And these carriers may act as a signi cant reservoir for the dissemination of CRKP in the healthcare facilities [42~44].Combined with our study, active surveillance for detecting CRKP colonization is critical for preventing the CRKP from spreading.…”
Section: Discussionsupporting
confidence: 92%
“…And our data indicated that ST37 were the main epidemic clones in the Neonate Ward, which showed consistency with what found in other studies [19,38]. It was discovered that ST37 are presumably to be a potential high-risk MDR K.pneumoniae clonal lineage [39].Furthermore, it is reported that carriage of carbapenem-resistant K. pneumoniae (CRKP) in the GI tract may precede and possibly serve as a source for subsequent clinical infections in approximately 9% of carriers [40,41]. And these carriers may act as a signi cant reservoir for the dissemination of CRKP in the healthcare facilities [42~44].Combined with our study, active surveillance for detecting CRKP colonization is critical for preventing the CRKP from spreading.…”
Section: Discussionsupporting
confidence: 92%
“…Plasmids with the R repB gene alone are apparently nonconjugative, lacking tra genes, and no relaxase gene has been identified (267). This may explain why complete plasmid sequences with R repB often have an additional replicon including FII K , A/C, or untyped rep genes (267,268). The original report of pK245 (266) also noted that repB is closely related to the ␤ replicon of pGSH500 (isolated from K. pneumoniae in/prior to 1991), which also carries an FII-like (␣) replicon (269).…”
Section: Resistance Plasmids In the Enterobacteriaceaementioning
confidence: 99%
“…Therefore, we should also pay close attention to the sporadic ST in addition to the major epidemic clone complex. It was discovered that ST37 are international clones associated with multidrug-resistant K. pneumoniae such as extended-spectrum β-lactamase, AmpC or carbapenemase producers [26]. Recently, NDM-1-producing K. pneumoniae belonging to ST37 were reported in China [27], which indicated that multidrug-resistant K. pneumoniae ST37 have been identified in our country.…”
mentioning
confidence: 95%